Work-Family Conflict on Burnout: The mediating of Work Stress - Gita Widya; Mega Asri Zona (Human Resource Management Studies, 2021)
The goal of this study was to examine the impact of work-family conflict on burnout at PT. Bank Pembangunan Daerah Sumatera Barat, using job stress as a moderating variable. This study employs a quantitative approach. Employees of PT. Bank Pembangunan Daerah Sumatera Barat comprised the study's population. While the sample size was 155 workers. Data collection is accomplished by the distribution of questionnaires, and data processing is accomplished through the use of a smart PLS. Work family conflict has a positive and significant effect on burnout, work stress has a positive and significant effect on burnout, work stress has a positive and significant effect on burnout, and work family conflict has a positive and significant effect on burnout with work stress as a mediating variable, according to the findings of this study.